The association of leisure-time physical activity and active commuting with measures of socioeconomic position in a multiethnic population living in the Netherlands: results from the cross-sectional SUNSET study - de Munter Jeroen SL; Agyemang Charles; Brewster Lizzy M; Stronks Karien; van Valkengoed Irene GM (BMC, 2012)
Abstract Background In most European origin populations measures of socioeconomic position are positively associated with leisure time physical activity (LTPA), this is unclear for active commuting. In addition, these associations have scarcely been studied in ethnic minority groups, who often have a high cardiovascular disease risk. Because of the expected public health potential, we assessed the relationship of active commuting and LTPA with measures of socioeconomic position across two large ethnic minority groups in the Netherlands as compared to the European-Dutch population. Methods We included South Asian-Surinamese (n = 370), African-Surinamese (n = 689), and European-Dutch (n = 567) from the cross-sectional population-based SUNSET study (2001-2003). Active commuting and LTPA were assessed by the SQUASH physical activity questionnaire and calculated in square-root-transformed metabolic equivalents of task-hours/week (SQRTMET). Socioeconomic position was indicated by level of education (low/high) and occupational class (low/high). We used age-adjusted linear regression models to assess the association between physical activity and socioeconomic position. Results Compared to the European-Dutch men, South Asian-Surinamese men engaged in lower levels of commuting activity and LTPA, and South Asian-Surinamese women engaged in lower levels of LTPA than their European-Dutch counterparts. Differences between the African Surinamese and the European-Dutch were small. We observed a positive gradient in active commuting activity for education in European-Dutch men (beta high education was 0.93, 95%CI: 0.45-1.40 SQRTMET higher versus low education), in South Asian-Surinamese men (beta: 0.56, 0.19-0.92), but not in African-Surinamese men (−0.06, -0.45-0.33, p for ethnicity-interaction = 0.002). In women we observed a positive gradient in active commuting activity and occupational class in European-Dutch women, and less strongly in South Asian-Surinamese and African-Surinamese women (p for ethnicity-interaction = 0.02). For LTPA and socioeconomic position, we observed no statistically significant interaction by ethnicity. Conclusions The positive gradient for socioeconomic position observed in European-Dutch was less strong, in particular for active commuting, among the South Asian-Surinamese and the African-Surinamese. This indicates that the typical focus on physical activity interventions in lower socioeconomic groups could work for European-Dutch populations, but this strategy may not be entirely applicable in the ethnic minority groups.